2020
DOI: 10.21203/rs.2.10974/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of weight trajectory after bariatric surgery on co-morbidity evolution and burden

Abstract: Background Bariatric surgery, such as Roux-en-Y gastric bypass [RYGB] has been shown to be an effective intervention for weight management in select patients. After surgery, different patients respond differently even to the same surgery and have differing weight-change trajectories . The present analysis explores how improving a patient’s post-surgical weight change could impact co‑morbidity prevalence, treatment and associated costs in the Canadian setting. Methods Published data were used to derive statisti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Considerable differences have been reported in weight loss trajectory after bariatric surgeries ( 27 29 ). One previous analysis has characterized outcomes in comorbidity resolution according to trajectory ( 27 ) and another considered the cost implications of comorbidity evolution for RYGB in the Canadian setting ( 14 ). Outcomes across Canadian studies of RYGB were assessed ( Supplementary Materials, section 2 , Supplementary Table 3 ) to determine trajectory groups from the study of Courcoulas et al ( 27 ) that most closely resemble Canadian outcomes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable differences have been reported in weight loss trajectory after bariatric surgeries ( 27 29 ). One previous analysis has characterized outcomes in comorbidity resolution according to trajectory ( 27 ) and another considered the cost implications of comorbidity evolution for RYGB in the Canadian setting ( 14 ). Outcomes across Canadian studies of RYGB were assessed ( Supplementary Materials, section 2 , Supplementary Table 3 ) to determine trajectory groups from the study of Courcoulas et al ( 27 ) that most closely resemble Canadian outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study of patients in the Ontario Bariatric Network, a centralized management system for all bariatric surgery referrals in the province, noted the potential negative cost impact of prolonged presurgical patient workup and its contribution to patient attrition ( 11 ). Other modeling studies based on published data from Canada have sought to quantify the cost burden associated with the current standard of care in comparison to an improved complete SG bariatric surgery care pathway in Canada ( 13 ), and focused on the post-surgical period for RYGB ( 14 ). These studies identified potential savings in costs and reduced patient comorbidity with realistic improvements to the presurgical wait time and post-surgical weight loss trajectories.…”
Section: Introductionmentioning
confidence: 99%